Relationship between CD4+ count, serum inflammatory cytokines, and oral melanotic hyperpigmentation in newly diagnosed HIV-seropositive patients: a nested casecontrol study (2022)
Objective. Oral melanotic hyperpigmentation (OMH) in patients with human immunodeficiency virus (HIV) infection has been attributed to the use of antifungal or antiretroviral drugs, as well as HIV-induced cytokine dysregulation. This research aimed to determine the relationship between immunosuppression and cytokine dysregulation in newly diagnosed HIV-seropositive subjects with OMH. Study Design. The study was conducted among newly diagnosed HIV-seropositive patients at the Infectious Disease Clinic, Ibadan, Nigeria. The cases were patients with OMH matched for age and sex with control subjects without OMH. CD4+ count and cytokine levels (interleukin-6 and tumor necrosis factor-a) were compared between the cases and control subjects. SPSS version 21 software was used for data analysis. Results. Seventy newly diagnosed HIV-seropositive patients were studied, which comprised of 35 cases and 35 control subjects. The median CD4+ counts for cases and control subjects were 174 cells/mm3 (interquartile range [IQR], 57-250) and 324 cells/ mm3 (IQR, 107-424), respectively. Severe immunosuppression (CD4+ count, 200 cells/mm3) was found in over half of the study participants, being more prevalent among the cases than among the control group (P = .019). Serum cytokine levels did not significantly vary between the cases and control subjects. Conclusions. There was a significant association between HIV-OMH and severe immunosuppression in the newly diagnosed HIV-seropositive patients.